FND : the Hill channel partner decision - Nanni, Alfred J. (SAGE business cases., 2019)
The case centers on FND, a company that specializes in providing data storage solutions to its customers. The company offers two storage solutions, Parallax its premium solution and Herald its second-tier solution. Raphaella Munoz is the director of the Herald division and must strategize on how to increase market penetration and focus within FND on Herald.